2010
DOI: 10.1007/s12032-010-9673-2
|View full text |Cite
|
Sign up to set email alerts
|

Whether drainage should be used after surgery for breast cancer? A systematic review of randomized controlled trials

Abstract: A systematic review of randomized controlled trials (RCTs) was conducted to evaluate whether patients benefit from the suction drainage after axillary lymph node dissection (ALND) in breast cancer surgery. RCTs of drainage versus no drainage after ALND in women with breast cancer were retrieved from PubMed, EMBASE, Cochrane Library and Chinese Biomedical database. Two authors independently assessed the quality of included trials and extracted data. Odds ratio (OR) for dichotomous outcomes and mean difference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 29 publications
3
49
1
3
Order By: Relevance
“…Studies have shown that the omission of a drain is associated with a shorter hospital stay and less post-surgical pain, but also with an increase in seroma aspirations [2,3,4,5,6]. In the past, various risk factors like breast size, age, blood pressure, and number of tumor-infiltrated lymph nodes have been evaluated [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the omission of a drain is associated with a shorter hospital stay and less post-surgical pain, but also with an increase in seroma aspirations [2,3,4,5,6]. In the past, various risk factors like breast size, age, blood pressure, and number of tumor-infiltrated lymph nodes have been evaluated [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…22 There are data regarding lymph node dissection (LND) at other surgical sites, which suggest that drains reduce the incidence of seromas, as well as seroma volume and need for aspiration. 23 It is possible that the risk of seroma is related to the extent of LND performed. However, a high percentage of patients (83%) in the present study had LND with a median number of lymph nodes removed, exceeding those of most reported open RRP or RALP series.…”
Section: Discussionmentioning
confidence: 99%
“…Para evitar este acúmulo de linfa postoperatorio, el único método que ha demostrado ser eficaz hasta la fecha es la colocación de un drenaje en el lecho quirúrgico, que exteriorice el líquido y evite su acumulación 10 . Este drenaje debe ser mantenido en el tiempo hasta que su débito prác-ticamente desaparezca, lo que implica o una mayor estancia hospitalaria o la incomodidad del manejo del drenaje de forma ambulatoria [2][3][4] . Durante la disección axilar no sólo se seccionan los canalículos linfáticos, que originan la extravasación de la linfa al espacio intersticial, sino que la propia agresión quirúrgica desencadena una respuesta inflamatoria.…”
Section: Discussionunclassified
“…En la cirugía de la LA se coloca un drenaje en el hueco axilar, que se mantiene varios días con el fin de reducir la aparición de seroma y posterior sobreinfección a absceso axilar 2 . No obstante, el mantenimiento de este drenaje implica un aumento de la estancia hospitalaria hasta su retirada 3 o que el paciente sea dado de alta antes con el drenaje, lo que disminuye el confort y aumenta el impacto psicológico de la enfermedad 2,4 .…”
Section: Factores Asociados a Mayor Débito De Drenaje Tras Linfadenecunclassified